The Public-Private Relationship in Social Services: The Role of the Third Sector - Guiteras Mestres, Àngels (Cuadernos de Trabajo Social, 2012)
The strategic alliance between public administration and the Third Sector is key for the development of a management model for social services in general in the future, and specifically for the externalized management of services in which it acts as a protagonist, given the social solvency of the Third Sector and its ability to multiply public funds. The Third Sector is an emerging player and contributes efficiency and social cohesion. We should move forward in measuring its impact and specific value added by identifying the social clauses which are used in public procurement, in the strengthening and structuring of the sector as well as in the capitalization and professionalization of social entities. Some of the principal challenges of the public-private relationship are identified and some proposals for the future are put forth.
Keywords: Third Sector; public; efficiency; social clauses; social cohesion.